In AF, CV benefits of catheter ablation vs. medical therapy may vary by age - Almhri, Ali; Leong, Darryl P (Annals of internal medicine, 2022)
Bahnson TD, Giczewska A, Mark DB, et al. Association between age and outcomes of catheter ablation versus medical therapy for atrial fibrillation: results from the CABANA trial. Circulation. 2022;145:796-804. 34933570.SOURCE CITATIONBahnson TD, Giczewska A, Mark DB, et al. Association between age and outcomes of catheter ablation versus medical therapy for atrial fibrillation: results from the CABANA trial. Circulation. 2022;145:796-804. 34933570.